THE EFFECT OF COMMODITY SUPERCYCLE AND DOMESTIC MARKET OBLIGATION ON PROFITABILITY RATIO (NET PROFIT MARGIN, RETURN ON ASSET) CASE STUDY ON COAL MINING ISSUERS IN INDONESIA STOCK EXCHANGE - Muhammad Alfan Wildani (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
The Covid-19 pandemic has resulted in economic paralysis due to the economy and human mobility. This resulted in demand for commodities that occurred simultaneously with conditions that were already improving, causing the supply to be unable to meet demand because the world's industrialized countries continued to boost their economic activities. This led to a very large demand for commodities, opening up coalescing commodities in general which soared simultaneously and formed a super cycle in commodities. Coal commodities that occur very quickly are certainly very profitable for coal mining companies. Based on the results of the regression in the study, it shows an increase in the reference price of coal which in this study uses the price of coal at Newcastle Port. It can be seen that one point of increase in the price of coal will affect an increase of 0.173 in return on assets and 0.111 in the net profit margin of coal mining issuers listed on the Indonesia Stock Exchange. The influence of the independent variable supercycle commodities, which in this study uses coal samples and the Domestic Market Obligation (DMO) policy, proved to have an effect and positive value on the dependent variable.